2015
DOI: 10.1093/jxb/eru504
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and developmental expression profiling of gibberellin signalling components in Vitis vinifera

Abstract: HighlightCharacterization of grape GA signalling components and GA quantitation unveil the berry-size regulating DELLA, and show that differential organ responses stem from both VvDELLAs and endogenous GA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 59 publications
(85 reference statements)
6
52
0
Order By: Relevance
“…GA orchestrates a broad range of processes and many levels of regulation are known to be involved in determining GA-responses, including biosynthesis, metabolism and signalling [8, 78]. Our data and those of others [11, 79] showed that another level of regulation exists in terms of GA–GID1–DELLA binding capacity and preference.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…GA orchestrates a broad range of processes and many levels of regulation are known to be involved in determining GA-responses, including biosynthesis, metabolism and signalling [8, 78]. Our data and those of others [11, 79] showed that another level of regulation exists in terms of GA–GID1–DELLA binding capacity and preference.…”
Section: Resultssupporting
confidence: 71%
“…Conserved DELLA domain is essential for GA-GID1–DELLA interaction, since any deletion or point substitution results in loss-of-interaction ability despite the presence of GA [47, 49, 58, 75]. Recently, a grape DELLA protein, VvDELLA3, exhibiting high sequence similarity to PslRGA has been characterized [11]. Although, both VvDELLA3 and PslRGA share the disrupted DELLA domain, VvDELLA3 displayed selective interaction with VvGID1-like proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcript levels of VvGID1 s, VvDELLA s, VvSLY1 s, and VvGASA s were measured by quantitative real-time PCR (qRT-PCR) as previously described (Acheampong et al, 2015), while and VvGA2ox s, VvGA3ox s, and VvGA20ox s expressions were by qRT-PCR using EvaGreen DNA-binding dye (Biotium Inc., Hayward, CA, United States) on the 96.96 Dynamic Array Integrated Fluidic Circuits (IFCs) (Fluidigm, San Francisco, CA, United States). Expressions of genes were normalized to transcripts of previously characterized, non-GA regulated VvGAPDH (Reid et al, 2006; Giacomelli et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Full-length VvDELLA proteins, used as sizing standards to locate endogenous VvDELLA proteins, were also expressed and purified as previously described (Acheampong et al, 2015), and quantified using BSA standards.…”
Section: Methodsmentioning
confidence: 99%